2019
DOI: 10.1093/mnras/stz3068
|View full text |Cite
|
Sign up to set email alerts
|

The lensing properties of subhaloes in massive elliptical galaxies in sterile neutrino cosmologies

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 99 publications
(192 reference statements)
2
30
0
Order By: Relevance
“…For example, the normalized radial density of M 0 = [10 7.5 , 10 8.0 ] M WDM subhaloes at 30 kpc is twice that in CDM at radii <70 kpc, and in the [10 7.0 , 10 7.5 ] bin the normalized abundance is a factor of five times the CDM equivalent. 1 We thus recover the intriguing results found in Bose et al (2017) and Despali et al (2020).…”
Section: Radial Distributionssupporting
confidence: 77%
See 2 more Smart Citations
“…For example, the normalized radial density of M 0 = [10 7.5 , 10 8.0 ] M WDM subhaloes at 30 kpc is twice that in CDM at radii <70 kpc, and in the [10 7.0 , 10 7.5 ] bin the normalized abundance is a factor of five times the CDM equivalent. 1 We thus recover the intriguing results found in Bose et al (2017) and Despali et al (2020).…”
Section: Radial Distributionssupporting
confidence: 77%
“…Initial published constraints using stream gaps have made the assumption that the spatial distribution of subhaloes is the same in WDM as in CDM. While this assumption appears to work well for massive, luminous satellites (Newton et al 2020), it breaks down for dark, lower mass haloes as shown above and in Despali et al (2020). We investigate the implications of this result by comparing the CDM and WDM subhalo populations in the halo region where stellar stream gaps are analysed versus the population of all subhaloes out to 300 kpc.…”
Section: Radial Distribution: Implications For the Number Of Stream Perturbersmentioning
confidence: 87%
See 1 more Smart Citation
“…Our four Ns Boltzmann-derived power spectra have shallower 1 An alternative, public algorithm for calculating these momentum distributions was presented by Venumadhav et al (2016). It was shown briefly in Despali et al (2019) slopes than their V05 counterparts, and this difference correlates with L6. The V05 fit overestimates the power of the LA12 model for k < k hm by up to 10 per cent and the LA8 model by 20 per cent.…”
Section: Methods and Resultsmentioning
confidence: 90%
“…originally with β = −1.3 and γ = 2.7. Despali et al (2019) refit γ = 0.35 for LA8; this model has M hm = 1.28 × 10 8 M⊙. We compute our results for the top-hat measure of halo mass, MTH, as this is the measure computed by EPS.…”
Section: Methods and Resultsmentioning
confidence: 99%